Un-Haunted House : Spirits, Solid Citizens, and Babbitt - Russ Castronovo (Transatlantica)
By considering Sinclair Lewis’s 1922 novel, Babbitt, this essay examines the continuum between the paranormal and the normal, the supernatural and the natural. The lesson of Babbitt reveals how the occult is absorbed under the aegis of the normal, the regular, the conventional. By reading the novel in conjunction with other texts about spiritualism written in the early twentieth century, we can see how the potentially alternate reality glimpsed in trances, séances, or other spiritualist practice is readily brought into alignment with the singular reality of conventional middle-class existence. The middle-class home is decidedly un-haunted, resistant to notions that the “hidden self,” to borrow a phrase from William James, has any gothic recesses. The result is that the utopian longings associated with spiritualism are reconciled with the biography of the “solid citizen,” which, incidentally, was the working title for Babbitt.